Three new species of Colomastix Grube, 1861 (Amphipoda: Colomastigidea) from Todos-os-Santos Bay, northeastern Brazilian coast, with identification keys to Atlantic Ocean species - Silvany, Liz; Senna, André R. (Zootaxa, 2019)
Colomastigids are small, commensal marine amphipods distributed worldwide. Here we present descriptions of three new species of Colomastix Grube, 1861 from Todos-os-Santos Bay (Bahia state), and separately identification keys to males and females of all known Colomastix species from the Atlantic Ocean. Males of Colomastix iemanja sp. nov. can be distinguished from all others in the genus especially by the bifurcate apex of inner ramus of uropod 1, with highly asymmetric branches surrounded by a membranous-like structure. Males of Colomastix tubulosa sp. nov. can be distinguished from all others in the genus especially by the tube-like morphology of the apex of inner ramus of uropod 1, the morphology of the distalmost palmar process of gnathopod 2 and by the expanded inner ramus of uropod 2. Females of Colomastix iemanja sp. nov. and Colomastix tubulosa sp. nov. are the only species in the Atlantic with a pleated apex on dactylus of gnathopod 2, besides Colomastix trispinosa Silvany, Alves & Senna, 2019. Colomastix marielle sp. nov. can be distinguished from all other species in the genus by the elongate carpus of pereopod 5 of females and by the rudder-like morphology of the apex of inner ramus of uropod 1 of males. These three new species increase the number of Colomastix in the Atlantic from 18 to 21, and are amongst the first records of the suborder Colomastigidea Lowry & Myers, 2017 from Brazilian waters.